Climate Change Impact Mitigation Strategy to Improve Health Resilience of Coastal Communities in Bungkutoko Village, Nambo District, Kendari City, Southeast Sulawesi - Siti Nurfadilah H; Arya Eka Putra; Balqis Fadhilah; Rifa Riski Yanti; Ruqayyah Apriliana; Wa Ode Sitti Nurmulya; Wa Ode Fatimah Zuhra; Suci Putriana (Journal of Epidemiology and Health Science, 2025)
Abstract Background: The impacts of climate change are multifaceted and affect various dimensions of human life, including public health, both directly and indirectly. According to the Intergovernmental Panel on Climate Change (IPCC), global temperatures increased by approximately 0.15°C to 0.3°C between 1990 and 2005. Southeast Sulawesi is among the regions influenced by the El Niño and La Niña phenomena; however, limited research has been conducted to explore these effects in the area. Objective: This study aims to examine the relationship between climate change mitigation strategies and the enhancement of health resilience, particularly regarding disease incidence in Bungkutoko Village, Nambo District, Kendari City, Southeast Sulawesi. Methods: This research employed an analytical observational design with a cross-sectional approach. A total of 236 residents of Bungkutoko Village were selected as respondents. Data were collected using a structured questionnaire administered through the Epicollect application. Statistical analysis was performed using crosstabulation tests in SPSS software. Results: Univariate analysis revealed that 74.1% of respondents reported experiencing illness. Bivariate analysis indicated a significant association between climate change and disease incidence (p-value = 0.016 < 0.05), as well as between climate change mitigation efforts and disease incidence (p-value = 0.000 < 0.05). Conclusion: Collaborative efforts between the community and government are essential to mitigate the adverse impacts of climate change and to strengthen public health resilience, particularly in coastal areas. Keywords: Climate Change, Indonesia, Public Health, Global Temperature, Government